2022
DOI: 10.1073/pnas.2123432119
|View full text |Cite
|
Sign up to set email alerts
|

A model of autonomous interactions between hippocampus and neocortex driving sleep-dependent memory consolidation

Abstract: How do we build up our knowledge of the world over time? Many theories of memory formation and consolidation have posited that the hippocampus stores new information, then “teaches” this information to the neocortex over time, especially during sleep. But it is unclear, mechanistically, how this actually works—How are these systems able to interact during periods with virtually no environmental input to accomplish useful learning and shifts in representation? We provide a framework for thinking about this ques… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 110 publications
(163 reference statements)
0
26
0
Order By: Relevance
“…memory consolidation, recent studies have suggested that offline periods following learning may be important for memory integration processes as well [22][23][24][25] .…”
mentioning
confidence: 99%
“…memory consolidation, recent studies have suggested that offline periods following learning may be important for memory integration processes as well [22][23][24][25] .…”
mentioning
confidence: 99%
“…Other studies suggest that sleep selectively facilitates weakly learned information (e.g., Schapiro, McDevitt, Rogers, Mednick, & Norman, 2018). These findings suggest that SWS does not simply stabilize memories, and instead, it might play a more complex role, reorganizing representations of past experience (Lewis & Durrant, 2011;Singh, Norman, & Schapiro, 2022).…”
Section: The Selective Effects Of Sleep On Memorymentioning
confidence: 95%
“…It is noteworthy that other mechanisms may also potentially account for the integration of related information during sleep. For example, (Singh et al, 2022) simulated the alternation between SWS, during which the hippocampus trained the neocortex with newly acquired memory, and REM sleep, during which the neocortex primarily replayed the consolidated remote memory without influence from the hippocampus. Therefore, it is possible that the replay of semantic connections during REM sleep directly overwrites the impairment of non-targets caused by retrieval practice and leads to facilitation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Memory consolidation is a process that unfolds over timehowever, due to methodological restrictions, our understanding of the time course of memory reactivations within a single night and especially across multiple nights is still lacking. Recently proposed frameworks suggest that within a single night, the combination of high-fidelity replay of recent memories in early NREM sleep with lower-fidelity replay, and integration with more remote memories, in later REM sleep optimizes memory consolidation over time (e.g., [153,154]). However, experimental data from rodent and human research to verify these models are still lacking.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%